Qi stagnation and qi deficiency are associated with depression in college students - Xinzhu, Wang; Yuanchun, Huang (Frontiers in Public Health, 2024)
Objective: The current study aims to investigate the correlations between qi stagnation, qi deficiency, and depression levels among college students.Method: This study investigated 403 college students and measured their levels of depression, qi stagnation, and qi deficiency to analyze the relationship between these three variables. Pearson correlation and linear regression statistical techniques were utilized.Results: (1) On average, college students reported mild depressive symptoms; (2) college students manifested low levels of qi stagnation and qi deficiency. (3) There exists a strong positive correlation between qi stagnation and qi deficiency; (4) A moderate positive correlation is present between depression and both qi stagnation and qi deficiency among college students. All these results support the mechanism by which qi stagnation and qi deficiency contribute to depression in traditional Chinese medicine theory.Qi stagnation and qi deficiency are moderately associated with depression levels in college students. It is feasible to use traditional Chinese physical therapy for qi regulation to alleviate depressive symptoms among college students.